Species diversity in Friesea (Neanuridae) reveals similar biogeographic patterns among Antarctic Collembola. (17th April 2021) - Stevens, Mark I.; Greenslade, Penelope; D'Haese, Cyrille A.
Abstract: The pan‐Antarctic distributions of several collembolan species have been supported by morphology for over 120 years. However, for most species where molecular data are available, these are now known to belong instead to several species, and most classified as short‐range endemics. One such species, Friesea grisea, had a pan‐Antarctic distribution that has been in question, but until recently, specimens of F. grisea from the type locality on South Georgia have not been included in any molecular appraisal. Here, we compare the molecular identity of specimens of F. grisea, from South Georgia, with other Antarctic and sub‐Antarctic species using the mitochondrial COI gene. A Bayesian phylogenetic analysis for 14 species of Friesea from southern regions, including F. grisea sensu stricto with species previously identified as ' F. grisea ' ( F . antarctica, F. gretae and F. propria ) confirms the distinctness of the South Georgian specimens based on molecular data, and these results are confirmed morphologically. The genus Friesea is one of the most speciose genera of Collembola known in the Antarctic region, and we provide an annotated key (dichotomous and interactive versions) to all Friesea species in the sub‐Antarctic and Antarctica. We compare the biogeography of Friesea to other Collembola from the region to highlight our current understanding of species boundaries and island linkages.